Water-independent residential properties as a transformational solution to achieve water sustainability in desert cities?. (20th March 2019) - Forrest, Nigel; Stein, Zoë; Wiek, Arnim
Abstract: Cities in regions around the world, such as the Colorado River Basin, face severe water challenges and need solutions that deliver significant progress towards sustainable urban water systems. Real-world experiments help stakeholders learn about solutions and select the most promising for scaling and transfer, but the sustainability experiments literature lacks guidance on how solution case studies might be done. An analytical framework for sustainability solutions developed by the authors is applied in a case study of a water-independent house experiment in Tucson, Arizona to provide insight into whether it could be a transformational solution towards a city-scale sustainable water system. Findings indicate technical feasibility, despite the arid climate, with sustainable co-benefits, but city-scale transformational potential is limited by house size, cost, and cultural acceptability, with a risk of negative systemic effect. Further experimentation towards a more effective solution is seen as worthwhile and areas for improvement and exploration are suggested. Highlights: Water independent housing is evaluated as a transformational urban water solution. Experiments from Tucson, Arizona show technical feasibility in hot arid climates. City-scale take-up has significant physical, financial, and cultural limitations. Improvements are possible and offer substantial city water savings. Cost is competitive with local centralized supply augmentation proposals.